A Single Blind Parallel Arm Randomized Placebo Controlled Clinical Study to Assess the Effectiveness of Homoeopathic Medicines with Physiotherapy in Cases of Chronic Low Back Pain of Musculoskeletal Origin (Advancements in Homeopathic Research, 2024)
Chronic low back pain is common problem  worldwide. Low back pain is pain, muscle tension, or  stiffness and chronic persists for twelve weeks. Chronic low back pain is common problem  worldwide. Low back pain is pain, muscle tension, or  stiffness and chronic persists for twelve weeks. Objectives To assess the effectiveness of “homoeopathic  medicines with physiotherapy” as compared  to “placebo with physiotherapy” for pain  management in cases of chronic low back pain  of Musculoskeletal Origin on the basis of the  Pain Numeric Pain Rating Scale. To assess the effectiveness of “homoeopathic  medicines with physiotherapy” as compared  to “placebo with physiotherapy” for pain  management in cases of chronic low back  pain of Musculoskeletal Origin on the basis of  Questionnaire (RMQ). To ascertain the predominant miasm in cases  of chronic low back pain of Musculoskeletal  Origin.
Keywords: common; homoeopathic medicines; physiotherapy